GAYA KOMUNIKASI ORGANISASI KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI MAS AL-WASHLIYAH TANJUNG BERINGIN KAB. SERDANG BEDAGAI (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the principal's organizational communication style, the factors that influence it, and its role in improving teacher performance and the quality of learning at MAS Al-Washliyah Tanjung Beringin, Serdang Bedagai Regency. The study used a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation studies. The research participants consisted of one principal and two teachers. Data analysis was carried out using the Miles and Huberman interactive model which includes data reduction, data presentation, and drawing conclusions, while the validity of the data was guaranteed through triangulation of sources, techniques, and time. The results showed that the principal applied various communication styles, including direct communication (face-to-face), written communication based on digital media, persuasive communication, two-way communication, and empathetic communication. This communication style reflects participatory leadership that encourages teacher involvement in decision-making. Factors influencing the implementation of communication styles include leadership experience, interpersonal competence, school organizational culture, teacher characteristics, communication media, and institutional policies. This study concludes that the principal's organizational communication style plays a strategic role in increasing teacher motivation and work effectiveness, as well as creating a conducive and innovative learning climate